Compound heterozygous splicing variants expand the genotypic spectrum of EMC1‐related disorders. Issue 5 (27th February 2023) - Bryen, Samantha J.; Zhang, Katharine; Dziaduch, Gregory; Bommireddipalli, Shobhana; Naseri, Take; Reupena, Muagututi'a Sefuiva; Viali, Satupa'itea; Minster, Ryan L.; Waddell, Leigh B.; Charlton, Amanda; O'Grady, Gina L.; Evesson, Frances J.; et al.
Abstract: EMC1 encodes subunit 1 of the endoplasmic reticulum (ER) membrane protein complex (EMC), a transmembrane domain insertase involved in membrane protein biosynthesis. Variants in EMC1 are described as a cause of global developmental delay, hypotonia, cortical visual impairment, and commonly, cerebral atrophy on MRI scan. We report an individual with severe global developmental delay and progressive cerebellar atrophy in whom exome sequencing identified a heterozygous essential splice‐site variant in intron‐3 of EMC1 (NM_015047.3:c.287‐1G>A). Whole genome sequencing (WGS) identified a deep intronic variant in intron‐20 of EMC1 (NM_015047.3:c.2588‐771C>G) that was poorly predicted by in silico programs to disrupt pre‐mRNA splicing. Reverse Transcription‐PCR (RT‐PCR) revealed stochastic activation of a pseudo‐exon associated with the c.2588‐771C>G variant and mis‐splicing arising from the c.287‐1G>A variant. This case highlights the utility of WGS and RNA studies to identify and assess likely pathogenicity of deep intronic variants and expands the genotypic and phenotypic spectrum of EMC1 ‐related disorders. Abstract :